PENGARUH PENDAPATAN TRANSFER PUSAT, PENDAPATAN ASLI DAERAH DAN PEMBIAYAAN DAERAH TERHADAP BELANJA MODAL DAERAH PADA PEMERINTAH KABUPATEN/KOTA DI INDONESIA - Slamet Widodo (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2023)
The purpose of this journal is to analyze the influence of central transfer revenues, regional original revenue, and regional financing on the allocation of regional capital expenditure in 503 regency/city governments in the period of 2008-2021. The low allocation of local government capital expenditure is one of the factors for conducting this research. The data used is the realization value of the Regional State Budget (APBD) for the period 2008-2021. The methodology used is a fixed effect panel data regression model. The benefit of this study is to improve the quality of regional development planning to increase regional economic self-sufficiency for both central and local governments. The results show the fixed effect model is the best model, and PAD, PTP, and PBY variables significantly affect capital expenditure.